Volatile organic compounds (VOCs) in surface coating materials: Their compositions and potential as an alternative fuel. (1st March 2016) - Dinh, Trieu-Vuong; Choi, In-Young; Son, Youn-Suk; Song, Kyu-Yong; Sunwoo, Young; Kim, Jo-Chun
Abstract: A sampling system was designed to determine the composition ratios of VOCs emitted from 31 surface coating materials (SCMs). Representative architectural, automotive, and marine SCMs in Korea were investigated. Toluene, ethylbenzene, and xylene were the predominant VOCs. The VOC levels (wt%) from automotive SCMs were significantly higher than those from architectural and marine paints. It was found that target SCMs comprised mainly VOCs with 6–10 carbon atoms in molecules, which could be adsorbed by activated carbon. The saturated activated carbon which had already adsorbed toluene, ethylbenzene, and m -xylene was combusted. The saturated activated carbon was more combustible than new activated carbon because it comprised inflammable VOCs. Therefore, it could be an alternative fuel when using in a "fuelization system". To use the activated carbon as a fuel, a control technology of VOCs from a coating process was also designed and introduced. Graphical abstract: A fuelization of activated carbon saturated with volatile organic compound emitted from surface coating process. Highlights: The highest composition ratios of VOCs were found in automotive surface coatings. Most of VOCs were in a range of C6 – C10 in terms of the number of carbon. Used activated carbon saturated with VOCS from paints is potential fuel. Fuelizing industrial coating process helps save natural resources.